2023
DOI: 10.1038/s41467-023-38802-0
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of self-incompatibility due to genetic interaction between a specific S-allele and an unlinked modifier

Abstract: Breakdown of self-incompatibility has frequently been attributed to loss-of-function mutations of alleles at the locus responsible for recognition of self-pollen (i.e. the S-locus). However, other potential causes have rarely been tested. Here, we show that self-compatibility of S1S1-homozygotes in selfing populations of the otherwise self-incompatible Arabidopsis lyrata is not due to S-locus mutation. Between-breeding-system cross-progeny are self-compatible if they combine S1 from the self-compatible cross-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
4
1
Order By: Relevance
“…The co-dominance of S -haplogroups B and D was observed in pistils 18 , and a previous report pointed out that S -haplogroup D belongs to the most dominant “phylogenetic class“ 51 based on phylogenetic analysis of SRK sequences 32 . However, our crossing experiment showed the male dominance of B over D. Furthermore, the evolutionary reversal experiment of SCR-B showed that the mutation in SCR was responsible for the evolution of self-compatibility, not that in other known or unknown genes such as an S -unlinked modifier gene recently reported from a self-compatible population of A. lyrata 56 . In this study, we focused on the transgenic experiments of SCR but did not manipulate sRNA.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The co-dominance of S -haplogroups B and D was observed in pistils 18 , and a previous report pointed out that S -haplogroup D belongs to the most dominant “phylogenetic class“ 51 based on phylogenetic analysis of SRK sequences 32 . However, our crossing experiment showed the male dominance of B over D. Furthermore, the evolutionary reversal experiment of SCR-B showed that the mutation in SCR was responsible for the evolution of self-compatibility, not that in other known or unknown genes such as an S -unlinked modifier gene recently reported from a self-compatible population of A. lyrata 56 . In this study, we focused on the transgenic experiments of SCR but did not manipulate sRNA.…”
Section: Discussioncontrasting
confidence: 53%
“…Such transgenic restoration by introducing a single gene shows that the mutation in the gene is responsible for self-compatibility and that all other genes for self-incompatibility are functional. The self-incompatibility system of Brassicaceae involves many genes other than SCR and SRK , and therefore self-compatibility may be attributed to so-called modifier genes such as M- locus protein kinase gene that are not linked to S -locus 35 , or to an unknown locus in the self-compatible populations of A. lyrata 50 , 56 . Because the sRNAs regulating male dominance are located at the S -locus 28 , 30 , the self-compatibility mutation must be located at the S -locus for dominance to be linked.…”
Section: Introductionmentioning
confidence: 99%
“…Resynthesized rapeseed lines exhibit self-incompatibility in the early generations, since they inherit functional S-alleles from both parent species, resulting in self-incompatibility in the offspring generations. The breakdown of self-incompatibility can occur due to not only loss-of-function mutations of alleles at the S-locus but also genetic interactions between specific S-alleles and unlinked modifiers 47 . In this study, although both parents of A and C genome used to produce the resynthesized lines were self-incompatible, self-compatible plants were selected during subsequent generations' selection processes and the self-compatibility trait improved in the advanced generations of the resynthesized lines.…”
Section: Discussionmentioning
confidence: 99%
“…This effort was essential to understand some of the evolutionary processes involved in the frequent transition of outcrossing to selfing mating systems in angiosperms (Barrett, 2002; Shimizu & Tsuchimatsu, 2015). It was also of value to breeders engaged in producing homozygous lines where SI is an undesired trait (Li et al ., 2023). However, the transition to selfing is also associated with changes in a combination of phenotypic traits, known as the selfing syndrome, and only a handful of studies have unraveled their genetic basis (Tsuchimatsu & Fujii, 2022).…”
Section: Introductionmentioning
confidence: 99%